Pengaruh Sosial Politik Pada Metodologi Penafsiran di Indonesia (Orde Lama, Orde Baru dan Reformasi) - Zulaiha, Eni; Agustin, Kartini Fujiyanti; Rahman, Nida Al (Hanifiya: Jurnal Studi Agama-Agama, 2022)
This paper tries to further examine the responses of commentators in the midst of the upheavals of the government during the Old Order, New Order, and Reformation eras. Interpretation which is a human product can be used as a parameter of Islam that the government running is state is in accordance with the teachings or not, so that in these three periods a continuous commentator was born with the politics that was going on at that time. The method used in this research is descriptive analysis based on library research. The findings of this study are that from the three periods of power, namely the Old Order, the New Order, and the Reformation, the are similarities in the style of interpretation used, namely Adab Ijtima’i, but different from the method of interpretation used, namely in the Old Order period, the method of interpretation used is the Tahlili method while the next two perioeds, namely the Thematic method according to the development of interpretation at that time.